2015
DOI: 10.1186/s12898-014-0033-5
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the invasive plant mile-a-minute (Mikania micrantha) by local crop sweet potato (Ipomoea batatas) by means of higher growth rate and competition for soil nutrients

Abstract: BackgroundThere are a variety of ways of increasing crop diversity to increase agricultural sustainability and in turn having a positive influence on nearby natural ecosystems. Competitive crops may provide potent management tools against invasive plants. To elucidate the competitive mechanisms between a sweet potato crop (Ipomoea batatas) and an invasive plant, mile-a-minute (Mikania micrantha), field experiments were carried out in Longchuan County of Yunnan Province, Southwest China, utilizing a de Wit repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
77
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 33 publications
3
77
1
Order By: Relevance
“…Variability of the non-storage root weight depends on the growth and development of the sweet potato genotypes. The findings of the present study agrees with the agreement of Naskar and Chowdhury (1994) and Shen et al (2015) who stated that the adventitious root weight ranges from 1-2 g. Similarly, dry weight of on-storage root differs significantly among the sweet potato genotypes. The maximum dry matter of fibrous roots was recorded in the genotypes JSP-1 (3.73 g) which is statistically similar to JSP-6 (3.62 g) and the minimum dry weight found in JSP-2 (1.63 g) (Fig.…”
Section: Fresh and Dry Weight Of Non-storage Roots (G)supporting
confidence: 82%
See 1 more Smart Citation
“…Variability of the non-storage root weight depends on the growth and development of the sweet potato genotypes. The findings of the present study agrees with the agreement of Naskar and Chowdhury (1994) and Shen et al (2015) who stated that the adventitious root weight ranges from 1-2 g. Similarly, dry weight of on-storage root differs significantly among the sweet potato genotypes. The maximum dry matter of fibrous roots was recorded in the genotypes JSP-1 (3.73 g) which is statistically similar to JSP-6 (3.62 g) and the minimum dry weight found in JSP-2 (1.63 g) (Fig.…”
Section: Fresh and Dry Weight Of Non-storage Roots (G)supporting
confidence: 82%
“…The findings of the present experiment are in agreement with the findings of Choudhury et al (1986). Shen et al (2015) reported that number of vine plantG 1 ranges from 10.4-13.3 due to available nutrient present in soil. In the present study, vine number was not satisfactory because of the tip portion of vine dry in all the genotypes upto the maturity for the reason of acidic soil as a result new vine could not grow.…”
Section: Diameter Of Main Vine (Cm)mentioning
confidence: 99%
“…Although M. micrantha is found in various habitats, such as disturbed roadsides, wastelands, plantations and secondary forests in low-altitude valleys, barren farmlands, and orchards, as well as the sides of ditches and rivers (Zhang et al, 2004), some studies have shown that the species prefers humid environments (Murphy et al, 2013;Shen et al, 2015). However, the effect of soil moisture on its F I G U R E 1 The locations of 162 Mikania micrantha populations in drylands (dry habitats; n = 74), on riverbanks (wet habitats; n = 36), and in wetlands with shallow water (aquatic habitats; n = 52) in the Pearl River Delta region of Guangdong, China population size has rarely been addressed (Xu, Shen, Zhang, Li, & Zhang, 2013).…”
mentioning
confidence: 99%
“…Nectar-dwelling yeasts are known to influence the sugar concentration and composition of nectar4, and may also affect the mutualistic interaction among plants and pollinators5. Given that nectar-dwelling yeasts rely on pollinator visitation for movement from one flower to another6, diversity and dispersal of nectar-borne yeasts is closely related to pollinator activity and diversity789.…”
mentioning
confidence: 99%
“…It is known, however, that nectar sugar content, yeast thermal tolerance, and individual growth rates11 influence nectar yeast community composition. Moreover, multiple pollinator visits removing nectar content of the same flower impede the proliferation of slow growing yeasts, and may thereby select against the relatively slow growing generalists89. Next to these factors, the adaptation of yeast species to certain pollinators (e.g.…”
mentioning
confidence: 99%